Physical activity and quality of life in schoolchildren during the COVID-19 pandemic, Cañete, Peru - Meza Ramírez, Sagmer Galois (2023)
The COVID-19 pandemic has led to health measures that generate the adoption of more sedentary lifestyles that may have an impact on the quality of life of schoolchildren. The objective of the study was to determine the relationship between the level of physical activity and the quality of life of schoolchildren during the COVID-19 pandemic. The method used was observational, correlational, and cross-sectional, and it was carried out in a school in the province of Cañete, in Peru. The study included 183 female schoolchildren aged 15 to 17 years. Physical activity was measured with the short version of the IPAQ questionnaire and quality of life with the KIDSCREEN-27 questionnaire. The relationship between the variables was determined using Spearman's Rho statistic. The results showed a high level of physical activity (52.5%), but a low level of quality of life (51.9%). In the correlational analysis, physical activity was positively related to overall quality of life (Rho = 0.183; p = 0.018) and to the domains physical well-being (Rho = 0.289, p = 0.000), psychological well-being (Rho = 0.181, p = 0.014), social support and friends (Rho = 0.149, p = 0.044) and school environment (Rho = 0.175, p = 0.018), but it was not related to the domain autonomy and relationship with parents (Rho = 0.019, p = 0.800). It is concluded that schoolchildren who engage in regular physical activity show a weak increase in their corresponding quality of life level.